Safety and Efficacy in HIV-1-Infected Patients Treated with Ritonavir-Boosted Saquinavir Mesylate - Knechten, Heribert (Blackwell Publishing Inc, 2010)
OBJECTIVE: To evaluate the safety, tolerability, and efficacy of ritonavir-boosted saquinavir 1000/100 mg twice daily administered as a 500 mg film-coated tablet in HIV-1-infected patients. METHODS: In this open-label, observational, 24-week survey conducted in 8 European countries, eligible HIV-infected participants had been prescribed saquinavir/ritonavir in combination with other nonprotease inhibitor (PI) antiretroviral agents as part of their HIV treatment regimen. The safety (grade 3 or 4 adverse events [AEs]), tolerability (by an investigator-reported subjective rating system), and efficacy (the percentage of participants with <50 and <400 copies/mL HIV RNA and change from baseline in mean CD4+ cell count) were analyzed for the overall study population and 7 subpopulations. RESULTS: The enrolled population included 2122 participants with 1908 completing the study; 44 (2.1%) withdrew prematurely because of AEs, including 7 nontreatment-related deaths. There were 33 grade 3 or 4 AEs in 29 (1.4%) participants; 7 AEs in 7 (0.3%) participants were considered treatment-related. Tolerability was reported to be “very good” or “good” in 42% and 25% of participants, respectively. From baseline to week 24, the proportion of participants with HIV RNA <50 copies/mL increased from 31.2% to 47.6% and the proportion with <400 copies/mL increased from 42.5% to 61.4%; the mean CD4+ cell count increased by 75 cells/µL. In the subpopulation analysis, the greatest efficacy benefits occurred in participants who were treatment-naïve and in those not having received prior PI therapy. CONCLUSIONS: Treatment with the saquinavir 500 mg film-coated tablet resulted in few grade 3 or 4 AEs and was well tolerated and effective in a broad population of patients.